Compulsive buying scale: validity, reliability and its psychometric characteristics in our society - Yüncü, Zeki; Kesebir, Sermin (Journal of Dependence, 2014)
Objective: The aim of this study is to search the validity and reliability of compulsive buying scale belonging to Valence, d’Astous and Fortier on our language.Method: 10 cases diagnosed with impulse control disorder not otherwise specified (compulsive buying) and 100 cases diagnosed with bipolar disorder, which are in 8 weeks remission period, are taken into this study according to DSM-IV. Healthy individuals from our hospital staff are taken into this study. These healthy individuals do not have any psychiatric sympthoms and psychiatric treatment according to SCID-NP. This staffs are similiar to cases with bipolar disorder in terms of age and gender. Scale validity, internal consistency and reliability are stated by factor analysis and correlations. Susceptibility, specificity, prevalence and cut off point are determined by ROC curve.Results: The average point of compulsive buying scale in cases diagnosed with bipolar disorder and compulsive buying is higher than healthy individuals. Internal consistency of the scale is calculated as 0.80. This test disintegrates into 3 dimensions in factor analysis. Tendency to spend corresponds 22.5 % of the variance, reactive aspect corresponds 53 % of the variance and guilty correspondes 24.5 % of the variance. There found a strong relation between Compulsive Buying Scale and Baratt Impulsivity Inventory. There found a moderate relation between Compulsive Buying Scale and Beck Depression Inventory, Beck Anxiety Inventory. There exists a strong reverse correlation between Compulsive Buyins Scale and Rosenberg Self Esteem Scale. Scale sensitivity is determined as 0.790 and specificity is determined as 0.955 in ROC curve. According to this prevelance is determined as 9.6 % and cut off point is calculated as 42 and more in 95 % confidence interval.Conclusion: It is stated that compulsive buying scale distinguishes the cases diagnosed with bipolar disorder and compulsive buying from healthy individuals. Turkish forms of compulsive buying scale are acceptable. These forms are also short, simple, based on self report and easy to apply.
Keywords: Compulsive buying; validity; reliability